Population-based analysis of hospitalizations in a West-European region revealed major changes in hospital utilization for patients with systemic lupus erythematosus over the period 2001–2012. (January 2016) - Piga, M; Casula, L; Perra, D; Sanna, S; Floris, A; Antonelli, A; Cauli, A; Mathieu, A
Objective: The objective of this paper is to evaluate hospital admissions in systemic lupus erythematosus (SLE) patients through a retrospective population-based study analyzing hospitalization data during 2001–2012 in Sardinia, an Italian region with universal health system coverage. Methods: Data on the hospital discharge records with the ICD-9-CM code for SLE (710.0) were obtained from the Department of Health and Hygiene and analyzed, mostly focusing on primary and non-primary diagnosis and Diagnosis-Related Group (DRG) code. In order to establish the significance of the annual trend for number and type of primary and non-primary discharge diagnosis, the two-tailed Cochran-Armitage test for trend was applied. In order to estimate SLE prevalence, data from administrative database and medical records were assembled. Results: This study included 6222 hospitalizations in 1675 patients (87% women). Hospitalizations with SLE as primary diagnosis were 3782 (58.0%) and significantly decreased during the study period. The annual number of renal, hematologic and neuropsychiatric disorders as non-primary diagnosis associated with SLE remained constant; however, their percentage increased ( p  < 0.0001) because of a declining number of admissions for SLE without associated diagnosis and without complications. Hospitalizations with SLE as non-primary diagnosis showed a significant upward trend in number and percentage of cerebrovascular accident ( p  = 0.0004), acute coronary syndrome ( p  = 0.0004) and chronic renal failure ( p  = 0.0003) as underlying primary diagnosis, while complications of pregnancy, labor and childbirth ( p  = 0.3375), malignancies ( p  = 0.6608) and adverse drug reactions ( p  = 0.2456) did not show statistically significant changes. Infections showed an increasing trend between 2001 and 2012 but did not reach statistical significance ( p  = 0.0304). After correction for hospitalization (93.8%) and survival (91.1%) rates calculated over the study period, the 2012 SLE prevalence in Sardinia was estimated to be 99.3 per 100, 000 inhabitants. Conclusions: While overall hospitalizations for SLE patients declined, those for cerebrovascular accident, acute coronary syndrome and chronic renal failure as underlying primary diagnosis increased during the study period.